Switching of the Microglial Activation Phenotype Is a Possible Treatment for Depression Disorder - Zhang, Lijuan; Zhang, Jinqiang; You, Zili (Frontiers in Cellular Neuroscience, 2018)
Major depressive disorder (MDD) is a common emotional cognitive disorder that seriously affects people’s physical and mental health and their quality of life. Due to its clinical and etiological heterogeneity, the molecular mechanisms underpinning MDD are complex and they are not fully understood. In addition, the effects of traditional drug therapy are not ideal. However, postmortem and animal studies have shown that overactivated microglia can inhibit neurogenesis in the hippocampus and induce depressive-like behaviors. Nonetheless, the molecular mechanisms by which microglia regulate nerve regeneration and determine depressive-like behaviors remain unclear. As the immune cells of the central nervous system (CNS), microglia could influence neurogenesis through the M1 and M2 subtypes, and these may promote depressive-like behaviors. Microglia may be divided into four main states or phenotypes. Under stress, microglial cells are induced into the M1 type, releasing inflammatory factors and causing neuroinflammatory responses. After the inflammation fades away, microglia shift into the alternative activated M2 phenotypes that play a role in neuroprotection. These activated M2 subtypes consist of M2a, M2b and M2c and their functions are different in the CNS. In this article, we mainly introduce the relationship between microglia and MDD. Importantly, this article elucidates a plausible mechanism by which microglia regulate inflammation and neurogenesis in ameliorating MDD. This could provide a reliable basis for the treatment of MDD in the future.